Bentuk Warning Label (Pictorial, Information and QuestionWarning Label) untuk Menurunkan Intensi Mengkonsumsi Mie Instan pada Mahasiswa di Kota Malang - Sumi Lestari; Selly Dian Permatasari; Yulizar Perwira Dara (Jurnal Psikologi Integratif, 2016)
The aim of this research is to discover the most effective warning label to decrease the intensity of instant noodle consumption on college student in Malang. This research used survey method by giving questionnaires to 1000 students, consisted with 477 male students and 523 female students from four universties in Malang, among them are 262 from Universitas Brawijaya, 235 from Universitas Islam Negeri Maulana Malik Ibrahim Malang, 300 from Universitas Negeri Malang, and 203 from Universitas Muhammadiyah Malang, with age ranged from 17-22 years old. The result shows that 228 students, about 22.8% chose information warning label as the most effective, 551 students, about 55.1% chose pictorial warning label as the most effective, and 221, about 22,1% chose question warning label as the most effective warning label to decrease the intensity of instant noodle consumption.